Bach's Works for Solo Violin: Style, Structure, Performance - Lester, Joel (Oxford Oxford University Press, 1999)
J. S. Bach's sonatas and partitas for solo violin have been central to the violin repertoire since the mid-eighteenth century. This engaging volume is the first comprehensive exploration of the place of these works within Bach's music: it focuses on their structural and stylistic features as they have been perceived since their creation. Joel Lester, a highly regarded scholar, teacher, violinist, and administrator, combines an analytical study, a full historical guide, and an
Keywords: Bach, Johann Sebastian -- 1685-1750; 18th Century (1701-1800); Violin; Sonata; Suite; Musical style; Musical analysis; Musical interpretation; Germany